Influence of Child Labour on Primary School Pupil's Enrolment and dropout: A Scoping Review - Amos Nnaemeka Amedu; Osita Victor Ossai (Fakultas keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kendari, 2023)
Child labour is one of the major obstacles to the realization of universal primary education in low- and middle-income countries. Child labour deprives children of their chances to acquire the required skills for the development of their potential. This is akin to a child trying to prepare for an exam while carrying a heavy backpack of worries, fears, and distractions on their back which affects their desired outcome. This study provided an updated review of the literature on child labour's influence on primary school pupils' enrolment. Child labour literature was explored via a scoping literature review strategy. As a result of this literature review, child labour negatively impacts primary school enrolment. This study also revealed that child labour is the major contributor to primary school pupils' dropout. Finally, this review revealed that enforcing a minimum employment age of 15 and reducing the return to child labour without providing social supports such as conditional cash transfer to the poor household would facilitate an increase in children's dropout rate in developing countries. Based on the empirical child labour literature, more research is needed to be conducted using qualitative and quantitative measures to capture first-hand information to augment quantitative measures.